ChemInform Abstract: Amphiphile Catalyzed Selective Synthesis of 4‐Amino Alkylated‐1H‐pyrazol‐5‐ol via Mannich Aromatization Preferred to the Knoevenagel—Michael Type Reaction in Water. Issue 18 (May 2015) - Kumar, Atul; Maurya, Shivam; Gupta, Maneesh Kumar; Shukla, Ratnakar Dutt
Abstract Sodium dodecyl sulfate is found to be a very useful amphiphile to catalyze the multicomponent reaction of aromatic aldehydes, 3‐methyl‐1‐phenyl‐5‐pyrazolinone, and secondary amines in aqueous media leading to 4‐amino alkylated‐1H‐pyrazol‐5‐ol dervatives (IV) without the formation of a bis product or any side product.